Transposon‐Based Identification of Factors That Promote Campylobacter jejuni Nuclease Activity. Issue 12 (7th December 2021) - Callahan, Sean M.; Johnson, Jeremiah G.
Abstract: Nucleases are ubiquitous in pathogens and allow bacteria to acquire nucleotide nutrients, take up foreign DNA, induce tissue damage, degrade neutrophil extracellular traps, and modulate the host inflammatory response. Furthermore, nucleases can modulate numerous bacterial virulence factors, promoting bacterial growth and disease. To understand how bacteria can produce nucleases, an unbiased approach is needed to identify these systems. Campylobacter jejuni is the leading cause of bacterial‐derived gastroenteritis and utilizes numerous systems to damage host DNA. Therefore, it is imperative to identify C. jejuni nucleases to understand the molecular mechanism of both infection and pathology. Detailed protocols for a transposon insertion sequencing–based DNase agar screen, a quantitative PCR nuclease screen, and PCR transposon insertion confirmation are included in this article. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : DNase agar colony screen of Campylobacter jejuni transposon insertion sequencing library isolates Basic Protocol 2 : Quantitative PCR nuclease screen of transposon insertion sequencing library isolates Basic Protocol 3 : PCR transposon insertion confirmation